A typical bedside-to-bench investigation of leukemogenic driver MEF2D fusion reveals new targeted therapy in B-cell acute lymphoblastic leukemia. Issue 3 (20th July 2022) - Zhang, Hao; Meng, Guoyu
Abstract : B-cell acute lymphoblastic leukemia (B-ALL) is a malignant tumor originating from B-lineage lymphoid precursor cells. The incidence of B-ALL is about 80% in childhood acute leukemia and 20% in adults. In recent years, with standardized treatment guided by risk stratification, the long-term disease-free survival rate of children is about 80%, while that of adults is less than 40%. However, the specific pathogenesis of the newly identified B-ALL and the targeted therapy strategies have not been vigorously investigated. In this review, we highlight the recent breakthroughs in mechanistic studies and novel therapeutic options in DUX4- and MEF2D-subtype B-ALLs.